2021
DOI: 10.3389/fanim.2021.791228
|View full text |Cite
|
Sign up to set email alerts
|

Dairy Cattle Response to a Virtual Fence When Pasture on Offer Is Restricted to the Post-grazing Residual

Abstract: Pasture-based dairy systems rely on the accurate allocation of pasture to both meet livestock requirements and maintain the growth of herbage. Currently, physical fences are used to contain livestock however they can be labor-intensive to shift and maintain. Alternatively, virtual fence (VF) systems offer flexibility and real-time control of livestock location. Pre-commercial neckbands (eShepherd®, Agersens, Melbourne, VIC) emit a warning audio tone (AT) when a cow approaches a VF boundary, paired with an elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 11 Colusso et al (2021a) [ 210 ] Australia Experiments conducted with AGDs to evaluate the impact of feed restriction showed that the restriction of food may impact the exclusion of cows from a feed attractant, but later they quickly learnt to avoid receiving the electrical stimuli and stayed within the restricted zone. 12 Colusso et al (2021b) [ 211 ] Australia AGDs were successful in excluding cows from fresh pasture even when they were only provided with post-grazing residuals. However, there were individual variations in the number of stimuli received by animals and time spent in the exclusion zone.…”
Section: Table A1mentioning
confidence: 99%
“… 11 Colusso et al (2021a) [ 210 ] Australia Experiments conducted with AGDs to evaluate the impact of feed restriction showed that the restriction of food may impact the exclusion of cows from a feed attractant, but later they quickly learnt to avoid receiving the electrical stimuli and stayed within the restricted zone. 12 Colusso et al (2021b) [ 211 ] Australia AGDs were successful in excluding cows from fresh pasture even when they were only provided with post-grazing residuals. However, there were individual variations in the number of stimuli received by animals and time spent in the exclusion zone.…”
Section: Table A1mentioning
confidence: 99%
“…Cattle are routinely contained with electric fencing of numerous forms within grazing dairy farms. Virtual fencing is an encouraging future technology to implement with grazing dairy cattle because it has the potential to allow for remote improved pasture utilization, and reduced labor ( McSweeney et al, 2020 ; Colusso et al, 2021 ). Virtual fencing provides for boundaries for cattle without using a physical barrier.…”
mentioning
confidence: 99%
“…A study in Australia evaluated neckbands for cows (eShepherd, Agersens Pty Ltd.) that produced a warning audio signal and electrical pulse for virtual fencing systems ( Colusso et al, 2021 ). The authors concluded that cows may be contained from fresh pasture forage for 24 h with virtual fencing.…”
mentioning
confidence: 99%